Investigation of Chlorophyll Mutations in Gamma Irradiated Naked Barley Genotypes - Saime İkincikarakaya; Güray Akdogan; Namuk Ergün (Journal of Advanced Research in Natural and Applied Sciences)
The consumption of naked barley is significantly increasing as more people become aware of its benefi-cial role as a source of dietary fiber and β-glucan. As a result, breeding programs paid more attention to naked barley. Improvement of yield and quality of naked barley is hindered by the lack of available germplasm. Mutation breeding is an effective tool for generating variation for plant breeding. Chlorophyll mutations are often used as visual indicators in breeding research to determine the optimum mutagen dosage. The purpose of this study was to identify the types and frequency of chlorophyll mutations brought on by different gamma radiation doses in two genotypes of hulless barley and determine the effective dose (ED50) based on the mutation frequency. Seeds of naked barley line YAA7050-14 and cv. Yalin that have been irradiated with doses of 100, 150, 200, and 300 Gy gamma rays delivered by a Cobalt-60 source. Chlorophyll mutations were observed in 8-day-old M2 plants grown under greenhouse conditions. In the M2 plants of cv. Yalin, the highest mutagen frequency was observed at 250 and 300 Gy, while in line YAA7050-14, the highest mutation frequency was found at 300 Gy. The rate of chlorophyll mutation rose in both genotypes as the gamma ray doses increased. The albino type of chlorophyll muta-tion was found in the cv. Yalin at the greatest rate, whereas the xantha type was found in the line YAA7050-14. The most common chlorophyll mutation type was albino, while the least common type was viridis when both genotypes were considered together. Based on the mutation frequency, 250-300 Gy doses could be used to effectively in further research to create mutations in the naked barley genotypes.